Role of Husband in Maternal Health Care in Muslim Community - Gautam, Jentil (Academia Research Journal, 2022)
The objectives of the study were to examine the ‘Role of husband in maternal health care in Muslim community. This study has been based on descriptive research design and it is quantitative in nature. In this study samples were collected by using stratified sampling method. The interview schedule was the main tool for data collection in this study. After collection information it was tabulated in chart diagram and analyzed and interpreted with the help of percentage. The findings of the study show that the socio-economic status of the people in that community is very low and hence the literacy rate is also low. Out of total 87 Muslim respondents 42.52 percent respondents were heard about maternal care and 57.47 percent respondent were not heard maternal cares. The conclusion of this research was Muslim women don’t get proper maternal care by their husbands.